Faktor yang Mempengaruhi Pelanggan Membeli di Toko Fashion Wanita @Tuku2store Jember - Citra Resmi Dewi; Jekti Rahayu; Haris Hermawan (Journal of Management and Bussines (JOMB), 2023)
This study aims to determine the effect of online promotions via Instagram, product quality and trust on purchasing decisions at the @Tuku2Store Jember store. The research method used in the form of observation, interviews and questionnaires to 97 respondents with purposive sampling technique, for data collection. The results of the study show that online promotion variables via Instagram, product quality and trust all have a positive effect on purchasing decisions. From the t test, the results of online promotion via Instagram, product quality and trust, all have a significant effect on purchasing decisions. The conclusion of the research is the better online promotion through Instagram, product quality and trust will increase purchasing decisions. Keywords: Online Promotion, Product Quality, Trust, Purchase Decision